Extradição e os desafios da cooperação internacional em matéria penal no Brasil - Merloti, Augusto Fávero [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The constant globalization of States and the growing relations between nations provide a great development for the international community as a whole, however, along with commercial and people exchanges, criminality has also transcended from territorially crimes to transnational crimes, a situation in which nations are obliged to adopt mechanisms of international cooperation in criminal matters. Thus, this work deals with international criminal cooperation in the Brazilian context, with a special focus on the current challenges of national jurisprudence for the institute of extradition, a controversial mechanism, but extremely important for international criminal cooperation. Thereby, the study sought to observe the phenomenon of international cooperation and extradition, through a bibliographical survey, as well as a research on the jurisprudence of the Federal Supreme Court, the competent Court for the matter of extradition. At the end of the work, it was observed that although Brazil has cooperation mechanisms and has assumed commitments with several countries, the lack of definition of political crime and the understanding of the President of the Republic's discretion to carry out an extradition allow the possibility of Brazil not complying with its duties and obligations to cooperate criminally before an international community.

A constante globalização dos Estados e as crescentes relações entre nações proporcionou um grande desenvolvimento para a comunidade internacional como um todo, entretanto, em conjunto com as trocas comerciais e de pessoas, a criminalidade também transcendeu de crimes territorialmente localizados para o âmbito transnacional, situação na qual as nações se veem compelidas a adotarem mecanismos de cooperação internacional em matéria penal. Desse modo, o presente trabalho aborda sobre a cooperação internacional criminal no âmbito brasileiro, com especial foco para os atuais desafios da jurisprudência nacional para o instituto da extradição, mecanismo polêmico mas de extrema importância para a efetiva cooperação penal internacional. Assim, o estudo buscou observar o fenômeno da cooperação Internacional e da extradição, por meio de um levantamento bibliográfico, assim como pesquisa de jurisprudência da Suprema Corte brasileira, Tribunal competente para a matéria de extradição. No fim do trabalho, foi observado que embora o Brasil detenha mecanismos de cooperação e de ter assumido compromissos perante uma diversa gama de países, a indefinição de criminalidade política e o entendimento sobre a discricionariedade do Presidente da República para cumprir com uma extradição, abrem a possibilidade do Brasil não cumprir com seus deveres e obrigações de cooperar criminalmente perante a comunidade internacional.
Extradition and the challenges of international cooperation in criminal matters in Brazil
Keywords: Cooperation; International; Criminal; Extradition; Cooperação; Internacional; Penal; Extradição